East and West Germany after the Unification The Wage Gap Analysis - Groero, Jaroslav (2015)
Under socialism workers had their wages set by the central planners.. In my thesis I use panel data from SHARLIFE questionnaire in order to analyze how returns to East German human capital variables changed after the reunification in 1990.I also compare these returns to West German returns to human capital variables. Before 1990 the returns to experience and education were lower in East Germany than in West Germany. After the reunification East German returns to experience obtained before 1990 and to education decreased. I find a significant decrease of returns to high educated workers who spent in the East German educational system 15 and more years. East German returns to both human capital variables are smaller than West German ones before the reunification and the difference is more pronounced after the reunification.